Putusan Mahkamah Konstitusi sebagai Tafsiran Resmi Hukum Islam di Indonesia - Alfitri, Alfitri (Mahkamah Konstitusi Republik Indonesia, 2014)
Unlike other Muslim countries, Indonesia does not make any reference to sharia as a source of legislation in its Constitution. Despite the fact, some aspects of sharia have been incorporated into Indonesian legal system. These “Islamic” state laws have been challenged by Muslims in Indonesia since their very first enactment in 1970s and now they find a new avenue to be settled with the institution of the Constitutional Court in 2003. This paper is to analyze what happen when a country such as Indonesia suddenly has to adjudicate disputes on which interpretation of Islamic law valid in Indonesia? In particular, it will assess methods employed by the Constitutional Court Judges in Indonesia in arbitrating contentions between conservative Muslims’ and the government’s claims regarding the extent to which Islamic law should be recognized, applied, and enforced by the state? Is the Court’s approach in settling down the cases still within the boundary of Islamic legal theory?This paper argues that the Court does declare itself as the legal authority in Indonesia and, thus, it reserves for itself the power to interpret and restrict Islamic law as it sees fit with the state’s agenda. However,the Court does that by considering and utilizing the concepts and vocabularies in Islamic law to justify its decisions. Hence, the Court’s decisions fall within the scope of siyasa shar`iyya, and its interpretation of which Islamic legal norms effective in Indonesia can be justified accordingly.